(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: In Bangladesh among inherited genetic diseases, thalassaemias and haemoglobinopathies are common and cause significant morbidity and mortality and impose a heavy financial burden on our society. Through premarital testing it is possible to reduce the number of children affected with genetic or other blood transmitted diseases. Aim: This review aims to motivate the general populations and reanimate the interest of stakeholders involved in the management of inherited genetic disorders and put forward the recommendations and proposal for implementing premarital screening programmes in Bangladesh. Materials & Methods: Relevant literatures were retrieved from different journals and web pages to highlight the definition, advantages and importance of premarital screening, types of investigation in the screening programmes and system of implementing this programme. Discussion: Review of different literature indicates that premarital screening programme is a complex social, religious and moral issue generating legal concerns regarding the infringement of fundamental liberty, the right to marry and the implications of involuntary withdrawal of blood. In regions where inherited genetic disorders are high, knowledge and outcome of the diseases and uptake of voluntary counseling is low. This is probably because these disorders are greater in developing and under developed countries where literacy and level of understanding are low. Culture and individual attitudes also have a role in the success of testing. 103 JAFMC Bangladesh. Vol 10, No 1 (June) 2014 In Asia, voluntary premarital screening programmes began for inherited and sexually transmitted diseases in countries like China, Taiwan, Malaysia, India, Indonesia, Maldives, Singapore and Thailand but no data is available regarding premarital screening programmes in Pakistan, Nepal, Sri Lanka, Bhutan and Bangladesh. Conclusion: Paucity of resources and trained health professionals in the area of medical genetics are major impediments in implementing premarital screening programmes in Bangladesh. Besides, religious beliefs, cultural norms, social customs as well as illiteracy may be the other barriers in performing the premarital screening programmes in Bangladesh. But it is high time to undertake motivational programmes and pilot projects to implement the premarital screening programmes in order to reduce the inherited genetic disorders, especially thalassaemias and haemoglobinopathies. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22934 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014